Preparation of liquid yogurt in the presence of pectin and its formation mechanism - Zhang, Hongkai; Goff, H. Douglas; Liu, Chengmei; Luo, Shunjing; Hu, Xiuting (Food chemistry, 2024)
We had previously observed that adding pectin into milk before fermentation inhibited gelation of yogurt but did not affect the pH. Thus, this work aimed to prepare such liquid yogurt and clarify its formation mechanism. It was found that liquid yogurt was obtained in the presence of 0.10%–0.20% pectin. However, at lower or higher pectin concentrations, yogurt was gelled. Confocal laser scanning microscopy analysis demonstrated that 0.10%–0.20% pectin induced milk protein aggregating into separated particles rather than a continuous network, which explained why liquid yogurt was formed. Moreover, adding 0.10%–0.20% pectin into the casein micelle suspension induced aggregation of casein micelles at pH 6.8. After pH decreased to 4.3, casein micelles showed more aggregation but they were still separated particles, which was the same in the corresponding yogurt samples. These results suggested that pectin changed the aggregation mode of casein micelles and induced formation of liquid yogurt. When pectin at specific concentrations was added into milk before fermentation, the depletion interaction between pectin molecules and casein micelles induced aggregation of casein micelles into the separated particles under the neutral condition and this structure was maintained after acidification to pH < 4.6. As a result, the liquid yogurt was formed. [Display omitted] •Adding 0.10%–0.20% pectin into milk before fermentation inhibited gelation of yogurt.•Adding pectin did not affect the pH of yogurt.•Casein micelles aggregated into separated particles in liquid yogurt.